Air filtration and air purification apparatus - CECCHI, MICHAEL; MEZEZI, MONICA (2014)
An air filtration and air purification apparatus comprising: (a) an enclosure, (b) a first air channel and a second air channel, (c) a divider, (d) a first filter located in direct fluid communication with the first air channel and second air channel, (e) a first air blower and a second air blower, and (f) a control system.